A formação geográfica dos estudantes no curso de licenciatura em pedagogia da Universidade Federal da Paraíba - Santana, Anderson Santos de (2020)
The object of our investigation was the Pedagogy Degree Course of the Federal University of Paraíba (UFPB) for the modality of the Magisterium in Early Childhood Education and Initial Grades of Elementary School, High School and Normal Courses and in other areas that have pedagogical knowledge, in the face-to-face modality and that is active. The choice of this university took place, because it is responsible for forming a greater number of Pedagogues in the State of Paraíba. What we study concerns the formation of the future teacher and not the work developed by the pedagogues in the classroom. It is in this context that we analyze the geographical training offered to students in training by the Degree course in Pedagogy, in the face-to-face modality, aiming to understand the formative conception with its subjects in the teaching-learning process. Since the classroom is configured for us as a space in permanent construction and reconstruction, due to the uses, functions, configurations and organizations that it fulfills over the course of a day, month or year, we understand it as part of our field. This course is the basis for the training of many teachers working in Basic Education, they will be responsible for the training of an important number of children and young people in Paraíba and also in other Brazilian states. Given the choice of the university and, starting from the curricula of the course we studied, we selected a discipline as the center of our analyses, because this is one that aims to develop geography teaching methodologies, be mandatory and offered in all semesters. Thus, in addition to our research objectives already presented, we discuss the interconnection between the geographic content developed by Geography and Pedagogy through this discipline, and the perception that pedagogue students have about these geographical knowledge and their importance for teaching and in their processes of training as a teacher.